KONSEP PENDIDIKAN FAZLUR RAHMAN - Helva Zuraya (The Pontianak State Institute of Islamic Studies, 2013)
Fazlur Rahman was a historical scientist who developed himself in experience and thoughts along with the times and environment. His maturity in experience and thoughts made him an established figure as an objective and critical reformer even though he had to pay the price because he was accused as a westernizer, an orientalist, and even as a traitor of the Qur'an. The emergence of Rahman‘s ideas about the contribution to modernist Islamic education was based on his observations on the development of Islamic education in the modern era of Islam in several countries such as Turkey, Egypt, Pakistan and Indonesia, where he argued that it is still faced with a number of problems in education.